Risk factors for human infection with mpox among the Mexican population with social security - Vallejos Parás, Alfonso; Arriaga Nieto, Lumumba; Cabrera Gaytán, David Alejandro; Cacho Díaz, Bernardo; Jaimes Betancourt, Leticia; Hernández Bautista, Porfirio Felipe; Cruz Orozco, Oscar; Valle Alvarado, Gabriel; Moctezuma Paz, Alejandro; Rivera Mahey, Mónica Grisel (PloS one, 2025)
The 2022 mpox outbreak marked a significant shift in the epidemiology of this zoonotic disease, traditionally confined to Central and West Africa. With over 80 countries reporting cases, this outbreak was characterized by a rapid spread in non-endemic regions, leading to more than 70,000 confirmed cases globally. To quantify the cumulative incidence of mpox and identify associated factors of mpox among the Mexican population affiliated by the Mexican Social Security Institute during the 2022-2023 outbreak. A retrospective observational study using a cross-sectional survey to assess the cumulative incidence and factors associated with mpox. The cumulative incidence of laboratory confirmed mpox cases was calculated by dividing the number of confirmed cases by the insured population in the Mexican Social Security Institute as of mid-2022, per 100,000 individuals, this was analyzed by sex, age group, sexual orientation and people living with HIV. Logistic regression analyses were conducted to identify sociodemographic and clinical factors associated with mpox infection. A total of 2,956 probable cases were reported, with 1,744 (59%) laboratory-confirmed mpox cases. Most confirmed cases were male, with a median age of 32 years. The overall cumulative incidence was 4.05 per 100,000 persons, significantly higher in men and men who have sex with men. Logistic regression revealed that male sex was significantly associated with higher odds of laboratory-confirmed mpox. Age groups 30-34, 35-39, and 40-44 had an elevated risk of infection. Men who have sex with men showed a substantially increased likelihood of mpox, while individuals living with HIV were at higher risk compared to those without HIV. Key clinical predictors included fever, arm rash, and inguinal lymphadenopathy. The 2022 mpox outbreak revealed significant disparities in infection risk, particularly among men, men who have sex with men, and individuals living with HIV.